Implementasi Penggunaan Kubernetes Cluster Google Cloud Platform untuk Deployment Aplikasi Wiki.js - Haryo, Ahmad Kusumo; kusuma, chandra (Universitas Samudra, 2024)
Every company has its own digital product, with the rapid pace of digital technology and the needs of users, it requires companies to be able to deliver their digital services, so they are always available and can be accessed at any time. In order to present digital services that are available at any time and in large quantities, the developers in the company create applications according to the large number of requests and needs, this creates problems in several ways, for example the more applications, the more servers are needed, of course this adds costs to application development, besides that there are dependencies between one application and another are make the application experience problems when the developer releases the latest version of the application. Google cloud platform is one of the platforms cloud computing which has many services, such as Google Kubernetes Engine. Kubernetes is an orchestration technology container which allows developer for management of containers in large numbers, this can be the one-off benefit for the application, so that is not easy to experience downtime, because container itself has separate resources from other applications. In this research will be tested for implementation deployment wiki.js application via kubernetes. The trial results of this research are the wiki.js application which can be accessed by utilizing the Kubernetes cluster technology.